IDDF2022-ABS-0052 Effect of gut influence on the immune environment in pre-clinical HCC. (2nd September 2022) - Shen, Sj Sijie; Jackson, Miriam; Khatiwada, Saroj; Vijayan, Abhishek; Raposo, Anita; El-Omar, Emad; Behary, Jason; Zekry, Amany
Abstract : Background: The gut microbiota has been implicated in immune and metabolic responses central to hepatocellular carcinoma (HCC) growth and survival. However, whether manipulating the gut microbiota influences systemic and hepatic inflammation remains to be elucidated. Our study aims to assess in the pre-clinical model of HCC whether gut manipulation by faecal microbiota transplantation (FMT) influences the systemic and local immune responses associated with HCC. Methods: We utilised C57Bl/6J mice and the diethylnitrosamine (DEN)-high fat diet (HFD)-induced model of HCC. We used a validated and published protocol from our group to achieve gut decontamination by antibiotics, prior to successful engraftment of donor FMT from HCC patients (HCC FMT) or Healthy controls (Healthy FMT). Plasma cytokines were assessed by 28-plex cytokine array (MagPix®). At 37 weeks (HCC timepoint), tumours were separated from adjacent liver tissue and snap-frozen for qPCR analysis. OPAL multiplex immunofluorescence (IF) was performed on paraffin-embedded tissue sections. Results: All mice had established HCC at 37 weeks. With HCC FMT, there were significantly increased expression of Cd4, Cd8, Ifng, and Cxcl1 compared to Healthy FMT ( p <0.05). Multiplex IF staining confirmed that HCC FMT increased infiltration of CD4+/FOXP3+ T cells within tumour regions compared to adjacent liver, whilst Healthy FMT led to the enrichment of CD8+ T cells within tumour regions. Correspondingly, HCC FMT led to a CD4-predominant milieu in the peripheral circulation with increased plasma levels of IL-2, IL-4, & IL-17 compared to healthy FMT. Conclusions: The data confirm that gut manipulation influences the tumour and systemic immune environment, with HCC FMT enticing a CD4-predominant response and a gene expression profile which favours tumour invasion ( Cxcl1 ). In contrast, Healthy FMT led to increased CD8+ T cell infiltration into the tumour environment. Our findings provide insight into the critical role gut microbiota plays in modulating immune responses relevant to HCC progression or regression.